Cum grano salis. - Gesing, Martin; Henatsch, Martin; Oehlke, Andreas; Raschke-Stuwe, Ingrid; Rehkopp, Martin; Rudiger, Georg; Schramm, Uwe; Schulte, Susanne (Münster : Kulturforum Rheine e.V, 2004)
Beuse, Stefan ; Ernst, Jupp ; Knobloch, Joachim ; Kobus, Nicolai ; Neugebauer, Ursula ; Rojko, Uros ; Schale, Dietmar ; Schumacher, Gottfried ; Steger, Ales ; Turner, Seth ; Veldhues, Karin ; Velmeke, Anke
biog., tent. p. 104-107
Duits
Exhibition. Cum grano salis. Kloster Bentlage Rheine. Kulturforum Rheine. 20.06.2004 - 03.10-2004. i.s.m. GWK Münster
boek